Analysis of Vibration Energy Harvesting Performance of Thermo-Electro-Elastic Microscale Devices Based on Generalized Thermoelasticity - Ailing He; Tianhu He; Bingdong Gu; Yuan Li (Actuators)
Piezoelectric material structures with an excellent mechatronic coupling property effectively promote self-power energy harvesting in micro-/nano-electro-mechanical systems (MEMS/NEMS). Therein, the characteristics of the microscale and multi-physical aspects effect significant influence on performance, such as attaining a fast response and high power density. It is difficult to use the classical mechanical and heat conduction models to effectively explain and analyze microscale physical field coupling behaviors. The purpose of this study is to develop the piezoelectric thermoelastic theoretical model, firstly considering the non-uniform physical field. The generalized equations governing thermo-electro-elastic vibration energy harvesting in a microbeam model were obtained based on Hamilton’s principle and the generalized thermoelastic theory was developed by considering thermopolarization and thermal hysteresis behavior. After that, the explicit expressions for voltage and output power were derived using the assumed-modes method; meanwhile, effects such as the piezo-flexoelectric aspect, size dependence, etc. are discussed in detail. It was found that thermal and microscale effects significantly promote the voltage and output power. The research is also helpful for the design and optimization of self-powered and high-performance micro/nano devices and systems.